1990
DOI: 10.1063/1.459257
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of N(4S) atoms with NO and H2

Abstract: Reactions of N(4S) atoms with NO and H2 have been investigated using direct detection of N atoms by the atomic resonance absorption technique in a shock tube apparatus, where N(4S) is generated by photodecomposition of NO by 193 nm laser radiation behind reflected shock waves. The rate constant of the reaction, N+NO→N2+O (1) has been determined using pseudo first-order kinetic analysis to be k1=(1.3±0.3)×1013 (cm3 mol−1 s−1) over 1600–2300 K temperature range, which agrees very well with the estimation by Baul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
89
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 12 publications
14
89
1
Order By: Relevance
“…Koshi et al (1990), using NO as a source for N atoms, reported a slightly lower value for the reverse reaction rate over a narrower temperature range. Michael and Lim (1992) also studied the reverse reaction and derived the forward reaction rate coefficient expression 1.0 x 10 14 exp( -37988/ T) cm 3 mol-1 s-l .…”
Section: 6mentioning
confidence: 94%
“…Koshi et al (1990), using NO as a source for N atoms, reported a slightly lower value for the reverse reaction rate over a narrower temperature range. Michael and Lim (1992) also studied the reverse reaction and derived the forward reaction rate coefficient expression 1.0 x 10 14 exp( -37988/ T) cm 3 mol-1 s-l .…”
Section: 6mentioning
confidence: 94%
“…taken from NIST (Jodkowski et al 1999;Tsang 1987 taken from NIST (Koshi et al 1990;Fontijn et al 2006;Mebel et al 1999). The activation barriers of 16600 K, 7760 K, 3610 K (respectively) are set to 12115 K, 1802 K and zero re-…”
Section: Appendix A: Chemical Reaction Ratesmentioning
confidence: 99%
“…Thus, it is generally very difficult to determine the mechanism and the rate constant for the individual elementary reactions. Situation is the same for the reactions of N or C atoms which are usually very difficult to prepare at a standard temperature range covered by a shock tube technique, but such difficulty can be avoided with a laser photolysis (Davidson and Hanson 1990;Koshi et al 1990). An example of the time decay profile of N atoms measured by ARAS is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%